Electrical and physical properties of modified potassium sodium niobate ceramics prepared by molten salt synthesis - Chatchai Kruea-In (2018)
In the present work, molten salt method was applied to synthesize the 0.9875(K0.5Na0.5)NbO3-0.0125BiScO3(KNN-BS) powders. Pure phase of KNN-BS powder was obtained for a calcination temperature of 700°C which lower than a conventional mixed oxide method by 250°C. The KNN-BS ceramics were fabricated by a solid-state reaction technique. Effects of excess Na and K on the properties of the ceramics were investigated. The excess Na and K produced an increase in dielectric constant at the ferroelectric to paraelectric transition temperature as well as change the transition temperatures. Further, the ferroelectric behavior was also improved by the additives. © 2013 Copyright Taylor and Francis Group, LLC.